Pemberdayaan Anak Jalanan Berbasis Komunitas - Suryadi Suryadi (UIN Siber Syekh Nurjati Cirebon, 2016)
The street children is a common problem, because these problems arise from the social system that does not run optimally, low community awareness and government programs that have not completed running well. There are 3 models of empowerment by mapping goals namely micro, mezzo and macro intervention. Intervention micro methods (individual and family) is to provide direct assistance to children and families. Interventions to children is by tutoring, spiritual, guidance, and social guidance and also savings. Intervention to families by providing counseling and programs intervenstion. Mezzo method of intervention focuses on community and social environment by improving the welfare of society. Community involvement and community elements in empowering street children by motivating and arousing awareness through empowerment programs are directly in contact with the child by involving all stakeholders. Factors supporting that sense of kinship, enthusiastic street children, in cooperation with community elements, and adequate facilities.Key words : Support and empowement, street children, community